Pesticide exposure affects flight dynamics and reduces flight endurance in bumblebees. Issue 10 (29th April 2019) - Kenna, Daniel; Cooley, Hazel; Pretelli, Ilaria; Ramos Rodrigues, Ana; Gill, Steve D.; Gill, Richard J.
Abstract: The emergence of agricultural land use change creates a number of challenges that insect pollinators, such as eusocial bees, must overcome. Resultant fragmentation and loss of suitable foraging habitats, combined with pesticide exposure, may increase demands on foraging, specifically the ability to collect or reach sufficient resources under such stress. Understanding effects that pesticides have on flight performance is therefore vital if we are to assess colony success in these changing landscapes. Neonicotinoids are one of the most widely used classes of pesticide across the globe, and exposure to bees has been associated with reduced foraging efficiency and homing ability. One explanation for these effects could be that elements of flight are being affected, but apart from a couple of studies on the honeybee ( Apis mellifera ), this has scarcely been tested. Here, we used flight mills to investigate how exposure to a field realistic (10 ppb) acute dose of imidacloprid affected flight performance of a wild insect pollinator—the bumblebee, Bombus terrestris audax . Intriguingly, observations showed exposed workers flew at a significantly higher velocity over the first ¾ km of flight. This apparent hyperactivity, however, may have a cost because exposed workers showed reduced flight distance and duration to around a third of what control workers were capable of achieving. Given that bumblebees are central place foragers, impairment to flight endurance could translate to a decline in potential forage area, decreasing the abundance, diversity, and nutritional quality of available food, while potentially diminishing pollination service capabilities. Abstract : Using an experimental flight mill setup, we found that acute neonicotinoid exposure impaired flight endurance and affected flight velocity of Bombus terrestris workers. This study is the first to show such effects in a wild insect pollinator, with potential negative consequences for colony foraging capacity and pollination potential.